PENGARUH KUALITAS PELAYANAN ADMINISTRASI TERHADAP KEPUASAN MASYARAKAT - Haryanti, Haryanti; Hakim, Lukman; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to determine the influence of the level of community satisfaction with administrative services at the Duampanua sub-district office, Pinrang Regency. The method in this research uses quantitative research methods with descriptive research type. The data obtained was then analyzed using simple linear regression analysis. The results of this research show that the analysis of the service quality variable is in the very good category with an average of 84.6 and the analysis of the community satisfaction variable is in the very good category with an average score of 86.26. Based on the results of a simple linear regression test, it shows that the service quality variable has an effect of 0.96% on community satisfaction with a significant value of 0.000 at the Duampanua sub-district office, Pinrang Regency.